Prognostic Value of YTHDF2 in Clear Cell Renal Cell Carcinoma - Mu, Zhongyi; Dong, Dan; Sun, Mingli; Li, Liwen; Wei, Ning; Hu, Bin (Frontiers in Oncology, 2020)
m6A, the main form of mRNA modification, participates in regulating multiple normal and pathological biological events, especially in tumorigenesis. However, there is little known about the association of m6A-related genes with prognosis of ccRCC. Therefore, the prognostic value of m6A-related genes was investigated using Kaplan-Meier curves of overall survival (OS) with the log-rank test and Cox regression analysis. The differential expression of YTHDF2 mRNA in ccRCC and tumor-adjacent normal tissues, and associated with clinicopathological characteristics were also analyzed. The alteration of cancer signaling pathways was screened by GSEA (Gene Set Enrichment Analysis). Univariate analysis showed that 15 m6A-related genes (including YTHDF2) were closely related to prognosis. Multivariate analysis further confirmed that YTHDF2 could serve as an independent prognostic factor for the OS of ccRCC patients (P<0.001). Low-level expression of YTHDF2 had poor prognosis in ccRCC patients with lower TNM stage, age (>61), non-distant metastasis, non-lymph node metastasis, female and higher histological grade (P<0.05). Moreover, YTHDF2 expression in ccRCC tissues (N=529) is significantly lower than that of tumor-adjacent normal tissues (N=72, P=0.0086). Furthermore, GSEA demonstrated that AKT/mTOR/GSK3 pathway, EIF4 pathway, CHREBP2 pathway, MET pathway, NFAT pathway, FAS pathway, EDG1 pathway and CTCF pathway are altered in tumors with high YTHDF2 expression. Taken together, our results demonstrated that YTHDF2 (a m6A-related genes) could serve as a potential prognostic biomarker of ccRCC, and targeting epigenetic modification may be a novel therapeutic strategy for the treatment of ccRCC.